Prevalence of polypharmacy and associated side effects in individuals with metabolic dysfunction-associated steatotic liver disease (MASLD): a systematic review and meta-analysis - Rajna Golubic; Peter Fitzgerald; Sumantra Ray; Sarah Armes; Jenneffer Tibaes; Ramya Rajaram; Mark W Ruddock; Mary Jo Kurth (BMJ Nutrition, Prevention & Health)
Objectives Metabolic dysfunction-associated steatotic liver disease (MASLD) is a prevalent chronic condition often accompanied by multiple comorbidities requiring complex pharmacological management. This review aims to examine the prevalence of polypharmacy in patients with MASLD, alongside an exploration of reported associations with side effects and observed relationships with patient-reported outcomes.Methods We conducted a systematic review using MEDLINE, CINAHL, Embase, Cochrane CENTRAL and Scopus databases, supplemented by a grey literature search, from inception to August 2024. Inclusion criteria were randomised controlled trials, cohort studies or case-control studies that evaluated the prevalence of polypharmacy and its consequences in adults with MASLD. Three reviewers independently performed study selection and data extraction. The quality of included studies was assessed using the Newcastle-Ottawa Scale. The primary outcome was the prevalence of polypharmacy, with secondary outcomes including side effects and quality of life (QoL). A meta-analysis with a random-effect model was performed.Results Six studies were included, of which three (totalling 2194 participants) were used in a meta-analysis. Polypharmacy prevalence ranged from 25% to 89%, with a pooled prevalence of 81% (95% CI 59 to 93), I²=99.5%. Adverse outcomes associated with polypharmacy included increased risk of hepatic encephalopathy-related hospitalisations, reduced QoL across physical and mental health domains, and augmented liver disease progression, particularly in individuals with advanced MASLD. Commonly used medications, such as anticholinergics and insulin, were linked to significant symptom burdens and metabolic dysregulation. Risk of bias assessments revealed that 50% of included studies had high risk due to limitations in study design, such as cross-sectional design and inconsistent definitions of polypharmacy, which reduced the certainty of evidence.Conclusions Polypharmacy is highly prevalent in MASLD and associated with poorer clinical outcomes and reduced QoL. Interventions such as deprescribing programmes and enhanced medication management strategies are needed to mitigate risks and optimise patient care.